"Eggerthella timonensis" gen. nov. isolated from a human stool sample. (May 2017) - Bilen, M.; Cadoret, F.; Daoud, Z.; Fournier, P.-E.; Raoult, D.
Abstract: We report the main characteristics of "Eggerthella timonensis" strain Marseille-P3135 which was isolated from a stool sample of a healthy 8-year-old pygmy (Baka) girl.